What Does It Mean to Be an Interventional Radiologist? SIR and the Private Practice Initiative - Pyne, Raj (Seminars in Interventional Radiology, 2019)
The new interventional radiology (IR) residency training pathways seek to graduate physicians who are not only experts at imaging and technically savvy but clinically oriented doctors capable of preprocedural workup and postprocedural care. The goal is for compassionate IRs who are holistic in their treatment of the patient and their disease, not just an expert at the procedure. However, much of this new envisioned approach for the modern IR is contradicted by the stark reality that most IRs in practice today (and most of the job market) are in private practice, where resources for clinical care in reality may not be prioritized as much in this idealistic scenario. The Society of Interventional Radiology (SIR) has recently made it a priority to represent the unique needs and frustrations of IRs in private practice and hopefully find a solution to the imminent reality that is facing most practicing IRs and future graduates.
Keywords: interventional radiology; private practice; IR residency training pathway; job market; Society of Interventional Radiology